Mixed Intraepithelial Neoplasia—Well-Differentiated Neuroendocrine Tumor of the Gallbladder: A Hitherto Unreported Combination. (September 2021) - Kővári, Bence; Turkevi-Nagy, Sándor; Lauwers, Gregory Y.; Jiang, Kun
Adenocarcinomas and noninvasive intraepithelial neoplasms (either polypoid or flat) are the most common gallbladder tumors; however, neuroendocrine neoplasms (NENs) can also occur. The majority of NENs are represented by neuroendocrine carcinomas (NECs), while neuroendocrine tumors (NETs) are extremely rare in this location. Occasionally, NEN may present as a part of a mixed neoplasm, with a coexisting non-neuroendocrine component. The latest World Health Organization classification denotes these lesions as mixed neuroendocrine–non-NENs (MiNENs). A novel type of MiNEN, the mixed adenoma well-differentiated NET (MANET), has been increasingly recognized and reported. In such lesions, a dysplastic noninvasive neoplasm and a NET represent the exocrine and endocrine component, respectively. MANETs have mostly been identified in the colon, small intestines, and stomach. In this article, we report, we believe, the first case of mixed gallbladder neoplasm with both biliary intraepithelial neoplasia (BilIN) and NET components, which may be regarded as a variant of MANET. Given the expectably favorable prognoses of MANETs, it is imperative not to misdiagnose the infiltrative yet indolent neuroendocrine component as an invasive adenocarcinoma or a NEC.